2016
DOI: 10.1097/med.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for transgender medical and healthcare research

Abstract: Purpose of Review Transgender individuals experience unique health disparities but are the subject of little focused health research. This manuscript reviews current literature on transgender medical and mental health outcomes and proposes research priorities to address knowledge gaps. Recent Findings Published research in transgender health care consists primarily of case reports, retrospective and cross-sectional studies, involving largely European settings. Challenges to US-based transgender health resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 64 publications
2
99
0
1
Order By: Relevance
“…Elucidating the latter will foster a more explicit moral deliberation in which the potential therapeutic benefits of single treatment steps can be weighed against potential pitfalls. Finally, our findings underscore the call for sound qualitative and quantitative research to inform guidelines and best practices, along with follow-up research on experiences with the provided care (Deutsch et al, 2016; Feldman et al, 2016). …”
Section: Discussionsupporting
confidence: 52%
“…Elucidating the latter will foster a more explicit moral deliberation in which the potential therapeutic benefits of single treatment steps can be weighed against potential pitfalls. Finally, our findings underscore the call for sound qualitative and quantitative research to inform guidelines and best practices, along with follow-up research on experiences with the provided care (Deutsch et al, 2016; Feldman et al, 2016). …”
Section: Discussionsupporting
confidence: 52%
“…Clearly, more research is needed into the past or current hormone usage in transgender people who report pregnancy involvement using clinical samples of youth and young adults, rather than community samples that cover a wide array of topics in brief (Feldman et al, 2016). Given the small number of participants who reported that they were currently pregnant, our findings suggest that most of the transgender youth in our sample who reported a history of pregnancy 1 We thank an anonymous reviewer for suggesting to assess circumstance.…”
Section: Limitations and Future Directionsmentioning
confidence: 66%
“…The literature on the burden of these types of nonmental health chronic conditions in transgender individuals is very sparse, especially in the United States, and even more so for older transgender adults. 40 Two small studies have shown similar findings for cardiovascular disease and diabetes; however, the studies were both conducted only with transgender patients on hormone therapy, and effects varied by sex assigned at birth. 41,42 A narrative review provides additional examination of transgender people taking hormones and the risk factors for cardiovascular disease.…”
Section: Trans Medicare Beneficiaries and Chronic Conditions 407 Discusmentioning
confidence: 81%